2021
DOI: 10.3389/fonc.2021.742728
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting Pathological Complete Response to Neoadjuvant Chemoradiotherapy Using Semiquantitative Parameters Derived From Sequential PET/CT in Locally Advanced Rectal Cancer

Abstract: We evaluated the predictive value of semiquantitative volumetric parameters derived from sequential PET/CT and developed a nomogram to predict pathological complete response (pCR) in patients with rectal cancer treated by neoadjuvant chemoradiotherapy (nCRT). From April 2008 to December 2013, among the patients who underwent nCRT, those who were taken sequential PET/CT before and after nCRT were included. MRI-based staging and semiquantitative parameters of PET/CT including standardized uptake value (SUV), met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Their study assessed the SUVmax, TLG, and MTV before and after nCRT in 137 patients with rectal cancer which was locally advanced, and found that the post-SUVmax, post-TLG, and post-MTV values were smaller in the pCR group as compared to the non-pCR group. Multivariate analysis revealed that post-SUVmax, post-TLG, and post-MTV values were independent factors for pCR [31].…”
Section: Discussionmentioning
confidence: 96%
“…Their study assessed the SUVmax, TLG, and MTV before and after nCRT in 137 patients with rectal cancer which was locally advanced, and found that the post-SUVmax, post-TLG, and post-MTV values were smaller in the pCR group as compared to the non-pCR group. Multivariate analysis revealed that post-SUVmax, post-TLG, and post-MTV values were independent factors for pCR [31].…”
Section: Discussionmentioning
confidence: 96%
“…The predictive factors and the model also need to be validated in other large patient series, preferably prospective, and we will start with the RAPIDO [ 9 ] dataset. In this regard, other markers, serial examinations with MRI, PET-CT, and functional radiology measuring the tumour’s metabolic activity before and early during the treatment could improve the baseline model in the future [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that post-TLG had a negative predictive value of 92.59% for GR status in LARC patients, but did not show a predictive advantage in pCR status. In previous studies, there have been meaningful reports about MTV, ΔMTV and ΔTLG in predicting the responsiveness of LARC patients to nCRT ( 8 , 25 27 ). However, in our study, none of these three parameters was found to have meaningful predictive value in our study.…”
Section: Discussionmentioning
confidence: 99%